2021
DOI: 10.1140/epje/s10189-021-00095-w
|View full text |Cite
|
Sign up to set email alerts
|

Multi-component generalized mode-coupling theory: predicting dynamics from structure in glassy mixtures

Abstract: The emergence of glassy dynamics and the glass transition in dense disordered systems is still not fully understood theoretically. Mode-coupling theory (MCT) has shown to be effective in describing some of the non-trivial features of glass formation, but it cannot explain the full glassy phenomenology due to the strong approximations on which it is based. Generalized mode-coupling theory (GMCT) is a hierarchical extension of the theory, which is able to outclass MCT by carefully describing the dynamics of high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 66 publications
7
37
0
Order By: Relevance
“…To summarize, we have demonstrated that a multi-component GMCT formalism can be constructed for Brownian systems governed by a many-body Smoluchowski equation. A comparison of our presented results with recent work on multi-component Newtonian GMCT [24] shows that in the overdamped limit both hierarchies of equations are completely identical. This demonstrates that the non-trivial similarity between Brownian and Newtonian systems witnessed for standard MCT is maintained for GMCT.…”
Section: Hierarchy Of Equationssupporting
confidence: 58%
See 4 more Smart Citations
“…To summarize, we have demonstrated that a multi-component GMCT formalism can be constructed for Brownian systems governed by a many-body Smoluchowski equation. A comparison of our presented results with recent work on multi-component Newtonian GMCT [24] shows that in the overdamped limit both hierarchies of equations are completely identical. This demonstrates that the non-trivial similarity between Brownian and Newtonian systems witnessed for standard MCT is maintained for GMCT.…”
Section: Hierarchy Of Equationssupporting
confidence: 58%
“…Despite remarkable successes of MCT [1,16,18,45], several discrepancies between the theory and simulations or experiments still persist [31,[46][47][48][49], most notably an overestimation of the glass transition. Inspired by previous studies [19][20][21][22][23][24][25][26][27], we therefore seek to improve and generalize the theory by developing a separate equation for the 4point dynamic density correlations (and later on continuing the process for even higher order correlations). Since we believe the factorization to be the most severe approximation, we will retain the 4-point density correlations and only replace the irreducible evolution operator by a full one.…”
Section: Extending Towards Gmctmentioning
confidence: 99%
See 3 more Smart Citations